Detection of early demonstrations of erythrocytes' and thrombocytes' aggregation in case of development of arterial hypertension and dislipidemia with the help of mice in the model of these pathologies' consecutive formation - IRINA ALEKSANDROVNA SKORJATINA,; SVETLANA YURYEVNA ZAVALISHINA,; ALEKSANDR SERGEEVICH USHAKOV, (International Journal of Pharma and Bio Sciences, 2017)
In this work we investigated early pathology demonstrations in mice' plasma, erythrocytes and thrombocytes in conditions of experimental consecutive formation of arterial hypertension and dislipidemia. We took into investigation 68 male-mice of Vistar line at the age of 2,5-3 months.33 animals of them had never received any impact and composed control group. Mice included into experimental group (35 animals) were consecutively formed to have arterial hypertention, and then - dislipidemia. During the experiment these animals were investigated 5 times. We applied biochemical, hematological and statistical methods of investigation towards experimental and control mice. At once after the formation of arterial hypertension and dislipidemia mice were noted to have quick increase of lipids' peroxidation processes in plasma, early number rise of reversibly and irreversibly modified erythrocytes and rapid increase of thrombocytes' intravascular activity. While mice were being formed to have arterial hypertension and dislipidemia they were noticed to have gradual increase of lipids' peroxidation in erythrocytes and thrombocytes at the rise of their aggregation. Control mice were noted to have stable normal level of investigated biochemical and hematological characteristics. The results of the fulfilled investigation can serve the basis for understanding of the earliest changes in erythrocytes' microrheological features and thrombocytes' activity at the debut of arterial hypertension development and start of dislipidemia formation on its background. Referring to the received in the present work results we consider the following factors to be quite possible: effectiveness rise in search of prophylaxis varients of erythrocytes' microrheological features' worsening and increase of thrombocytes' activity at the start of arterial hypertension development and especially at the addition of dislipidemia to it.